1996
DOI: 10.1136/jnnp.61.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Campylobacter jejuni infection in the chicken: an animal model of axonal Guillain-Barre syndrome.

Abstract: Objective-To develop and characterise an animal model of paralytic neuropathy after Campylobacter jejuni infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 21 publications
2
49
1
Order By: Relevance
“…In light of the wide occurrence of anti-GSL Abs in these patients, recent research on GBS has focused on GSL mimicry between LPSs in C. jejuni and endogenous GSLs in the peripheral nervous system that may be involved in the pathological mechanisms of GBS (Ang et al, 2004). Strain HS19 of C. jejuni was isolated from GBS patients and paralytic chickens (Li et al, 1996) and found to be associated with 29% of C. jejuniassociated GBS patients in the United States and 83% of cases in Japan (Nishimura et al, 1997;Allos et al, 1998). Although GSL mimicry as a causative mechanism remains uncertain for GBS and related diseases, the terminal tetrasaccharides Galβ1-3GalNAcβ1-4(NeuAcα2-3) Galβ1-4 of a GM1-like epitope and NeuAcα2-8NeuAcα2-3Galβ1-4Hep of a GD3-like epitope have been chemically determined in the LPSs from HS19 (Aspinall et al, 1992(Aspinall et al, , 1994Yuki et al, 1993).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…In light of the wide occurrence of anti-GSL Abs in these patients, recent research on GBS has focused on GSL mimicry between LPSs in C. jejuni and endogenous GSLs in the peripheral nervous system that may be involved in the pathological mechanisms of GBS (Ang et al, 2004). Strain HS19 of C. jejuni was isolated from GBS patients and paralytic chickens (Li et al, 1996) and found to be associated with 29% of C. jejuniassociated GBS patients in the United States and 83% of cases in Japan (Nishimura et al, 1997;Allos et al, 1998). Although GSL mimicry as a causative mechanism remains uncertain for GBS and related diseases, the terminal tetrasaccharides Galβ1-3GalNAcβ1-4(NeuAcα2-3) Galβ1-4 of a GM1-like epitope and NeuAcα2-8NeuAcα2-3Galβ1-4Hep of a GD3-like epitope have been chemically determined in the LPSs from HS19 (Aspinall et al, 1992(Aspinall et al, , 1994Yuki et al, 1993).…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…Vriesendorp (1997) pointed out that the immune mechanisms by which infection with C. jejuni can create peripheral injury to axons instead of myelin should be studied. In this regard, Li et al (1996) were able to demonstrate development of paralysis in chickens infected with a strain of C. jejuni isolated from a human GBS patient who developed acute motor axonal neuropathy. One-third of the experimental chickens developed paralysis 5-18 days a�er oral administration of the C. jejuni culture.…”
Section: Gbs and C Jejunimentioning
confidence: 88%
“…C. jejuni infection appears to be closely associated with the axonal forms of GBS as reported from studies carried out in China and Japan. Li et al [36] described C. jejuni induced neuritis in chickens mimicking acute axonal neuropathy as seen in human AMAN (acute motor axonal neuropathy) when fed with C. jejuni O:19. But this association is not consistent in western countries where the cases of AMAN with antecedent C. jejuni infection are less than 10%.…”
Section: Discussionmentioning
confidence: 99%